From Integrating to Learning: Insights from Spanish L2 Multiple Documents Selection in Reading Tasks - Maha Soliman (Universidad de La Sabana, 2021)
Previous literature has focused on investigating the use of sources in the classroom and how much they contribute to building a coherent mental representation of the texts. These studies explain how integration from multiple document sources occurs; however, their results are limited to the first language and do not inform about the types of these sources or how they are used. In this sense, the objective of this case study is to identify the types of sources used in four courses of a student exchange program in a Chilean University. The data was collected through focus groups with sixty students and in-depth interviews with four professors to determine in what sense the type of document selected could contribute to the learning process. A content analysis was carried out using Nvivo 12 to report on the pedagogical implications of using these sources in a Spanish L2 teaching setting.